2003
DOI: 10.12968/hosp.2003.64.11.2353
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease and Crohn's disease: an association not to be forgotten

Abstract: A10-month-old girl presented with a 2-month history of diarrhoea, 5–6 times a day. She was otherwise healthy, had a good appetite, and was thriving on a normal infant diet. She was born at full term by normal delivery, birth weight being 3.29 kg (25th centile). Immunizations were up to date and the development was normal. There was no other relevant past history. Her father had Crohn's disease, her maternal grandmother had coeliac disease and her maternal grandfather had ulcerative colitis. She did not improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, in most cases, this association was incidental (e.g., diagnosis of celiac disease was made because of irreversible diarrhea in CD after anti-inflammatory therapy had started). [4][5][6][7] This is the first prospective study evaluating the prevalence of celiac disease in a consecutive series of patients affected by CD, and it leads to several interesting point of discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most cases, this association was incidental (e.g., diagnosis of celiac disease was made because of irreversible diarrhea in CD after anti-inflammatory therapy had started). [4][5][6][7] This is the first prospective study evaluating the prevalence of celiac disease in a consecutive series of patients affected by CD, and it leads to several interesting point of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…2 The lack of gluten in the diet generally leads to a return to normality of the morphologic changes. 3 Our recent experience 4 and some recent case reports [5][6][7] showed that there is a relationship between CD and celiac disease, but a prospective study has not been performed yet. The aim of our study was to evaluate the prevalence of celiac disease in a consecutive series of patients affected by CD, in whom the disease was diagnosed for the first time.…”
mentioning
confidence: 99%
“…However, during the last decade, the prevalence of IBD especially CRD in patients with celiac disease has increased continuously; this prevalence is 5 to 10 times more frequent than in the general population [1,4,5]. Unlike our two patients with different ages and sexes, the association of celiac disease and Crohn's disease affects most often the young male adult [1,4].…”
Section: Discussionmentioning
confidence: 73%
“…The association of Crohn’s disease and coeliac disease is of tremendous interest to physicians. More commonly Crohn’s disease is discovered after the pre-existing coeliac disease, yet the reverse has also been reported 9. Ig G anti-transglutaminase antibody may be found in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%